2014
DOI: 10.1016/j.eij.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements to knowledge discovery framework of SOPHIA textual case-based reasoning

Abstract: Many approaches were presented recently for developing Textual Case-Based Reasoning (TCBR) applications. One of the successful approaches is SOPHisticated Information Analysis (SOPHIA), which is distinguished by its ability to work without prior knowledge engineering, without domain dependency and without language dependency. SOPHIA is based on the distributional document clustering approach, which facilitates an advanced and rich knowledge discovery framework for case-based retrieval.This paper contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Moreover, in another work presented by the same authors [10], the only results shown are clustering results. However, neither the software applications nor the textual resources used in the experiments are available for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in another work presented by the same authors [10], the only results shown are clustering results. However, neither the software applications nor the textual resources used in the experiments are available for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…However, in [9], [10] Islam Elhelwany et.al. have proposed an Arabic Fatwa Intelligent system based on textual case based rezoning which was firstly used in [11].…”
Section: A Previous Workmentioning
confidence: 99%
“…• Enhancements to knowledge discovery framework of SOPHIA textual case-based reasoning [26] In [26] The same authors of the previous system have enhanced their previous study by adding one tier in the middle. This tier was created by manually clustering the dataset into several groups so the SOPHIA will be applied to each group separately and that what make an enhancement as they reported.…”
Section: B Qa Based On Faqmentioning
confidence: 99%
“…Textual Case-Based Reasoning (TCBR) is a CBR sub field that compares a problem with a set of past cases where the knowledge sources are available in textual format. Comparing text content is vital to identify relevant cases for solution reuse [9]. However, Textual information typically is hard to process by computers due to its relatively unstructured format and the numerous possible variations in its interpretation.…”
Section: Introductionmentioning
confidence: 99%